Electrocardiogram Derived QRS Duration >120 ms is Associated With Elevated Plasma Homocysteine Levels in a Rural Australian Cross-Sectional Population. Issue 27 (July 2015) - Leng, Yvonne Lee Yin; Zhou, Yuling; Ke, Honghong; Jelinek, Herbert; McCabe, Joel; Assareh, Hassan; McLachlan, Craig S.; Isazadehfar., Khatereh
<x xml:space="preserve">Abstract</x> Abstract Homocysteine levels in the low to moderate range for cardiovascular risk have been previously associated with left ventricular cardiac hypertrophy (LVH). Electrocardiogram (ECG) derived QRS duration has also been used as an epidemiological screening marker for cardiac hypertrophy risk. QRS duration cut offs have not been previously modeled to assess homocysteine levels in community populations. Our aims are to determine if QRS duration is associated with an elevated homocysteine level in a cross-sectional Australian aging rural population. A retrospective study design utilizing a rural health diabetic screening clinic database containing observational data from the period January 9, 2002 till September 25, 2012. One hundred seventy-eight individuals (>21 years of age) from the database were included in the study. Inclusion criteria included being nondiabetic and having both a QRS duration measure and a matching homocysteine level within the same subject. All participants were from the Albury-Wodonga area, with a mean age of >64 years for both sexes. Mean population homocysteine plasma levels were 10.4 μmol/L (SD = 3.6). The mean QRS duration was 101.8 ms (SD = 17.4). Groups were stratified on the basis of QRS duration (⩽120 ms [n = 157] and >120 ms [n = 21]). QRS duration subgroup (⩽120 ms vs >120 ms) mean differences across homocysteine levels were 10.1 μmol/L (SD = 3.3) and 12.2 μmol/L (SD = 4.7), respectively (P = 0.016). Other ECG parameters (PQ interval, QTc interval, and QT dispersion) measurements were not significantly associated with differences in plasma homocysteine (P = not significant). We conclude that in community populations homocysteine may be moderately elevated when QRS durations are >120 ms. Small additional increases in homocysteine levels may suggest a risk factor for ECG diagnosis of LVH.